A Comparative Study of Labour Productivity in Public, Private and Foreign Sector Banks in India. (September 2014) - Bhatia, Aparna; Mahendru, Megha
Productivity is the ability and willingness of an economic unit to produce maximum possible output with given inputs and technology. It is the quotient obtained by dividing output by one of the factors of production. Measuring productivity is very important for judging long-term operational viability of the banks. A bank's productivity is a measure of its effectiveness in using all its resources, viz. labour, financial resources, fixed assets etc. The present article evaluates and compares the productivity performance of the banks in India. All the public sector, private sector and foreign sector banks in India constitute the sample of the study. The study covers the time period of 11 years, that is, 2000–2001 to 2010–2011. The results show that foreign sector banks have the highest average for all the productivity parameters. The average for all these parameters is next highest for private sector banks (PVBs) whereas public sector banks (PSBs) have the lowest average. Even Analysis of Variance (ANOVA) test shows that the p value is significant at 1 per cent level of significance for all the ratios i.e., Deposit per Employee (DPE), Loan and Advances per Employee (LAPE), Business per Employee (BPE), Total Income per Employee (TIPE), Total Expenditure per Employee (TEPE) and Net Profit per Employee (NPPE). Further, the results of Post Hoc Tukey Test revealed that difference between the means of Foreign-Public sector and Foreign-Private sector banks is statistically significant for all the productivity parameters.